MOTIVATION AS A MEDIATOR OF KNOWLEDGE EFFECT ON INVESTMENT INTEREST - I Gusti Bagus Yosia Wiryakusuma; Tifania Angga (Accounting Study Program, Universitas Ciputra Surabaya, 2023)
The Covid-19 pandemic has made the Indonesian people aware of the importance of saving funds or being reserved for emergencies. Based on this fact, an investment phenomenon emerged where the number of investors increased from previous years. This study aims to determine the effect of investment knowledge and investment motivation on investment interest, with investment motivation as a mediator. The research sample is 100 respondents, where the respondents are investors who are domiciled in Surabaya. PLS-SEM was used to test the hypothesis of this study. The results indicate that investment knowledge influences investment interest and investment motivation. In addition, investment motivation also affects investment interest. Moreover, this study found that investment motivation can mediate the effect of investment knowledge on investment interest.